Industry—Challenge to Pro-Environmental Manufacturing of Goods Replacing Single-Use Plastic by Indian Industry: A Study Toward Failing Ban on Single-Use Plastic Access - Shabbiruddin; Neeraj Kanwar; Vinay Kumar Jadoun; Jayalakshmi N. S.; Asyraf Afthanorhan; Nuzhat Fatema; Hasmat Malik; Mohammad Asef Hossaini (IEEE Access)
One important topic that raised concern among researchers and population is the threat posed by the widespread presence of single-use plastic items, which has become a part of day-to-day life. An urgent need is to build a plan by manufacturers/ investors to give a due concern over environmental preservation. A number of challenges are yet to be addressed for implementation of sustainable manufacturing concerned with environment; this is a matter of worry. Prime minister of India on 150th anniversary of Mahatma Gandhi has urged the nation to make India free of single-use plastics. On July 1, 2022, India banned single-use plastic items that have low utility but are frequently littered around, such as plastic straws. Work done in this research is undertaken for finding the prominent challenges which are faced in the eco-friendly sustainable manufacturing practices in single-use plastic industries. It is also a matter of concern that why a ban on certain single-use plastic with low utility is failing in India?. A framework has been made on Triangular Fuzzy Number (TFN) based fuzzy method to identify and rank the associated problems/ challenges. Triangular fuzzy numbers are effective in modelling imprecise and uncertain information, and have been widely applied in decision making. In this work 13 challenges have been identified and ranking is done using TFN to find the most prominent factors. From results it is very clear that Expense on implication, Scantiness in the support received from the government and Lack of environment concern among suppliers are the most influencing factors/ challenges. Works done on identification of challenges will be of help to policy makers and industrialists in identification of core issues.